APPROACHING THE LEGENDARY HSUAN TSANG, THE PILGRIM AND SCHOLAR THROUGH THE LENS OF BIOGRAPHICAL CRITICISM - Thanh Trung Nguyen (Tạp chí Khoa học Đại học Đà Lạt, 2024)
Hsuan Tsang, the Pilgrim & Scholar by Venerable Thich Minh Chau is notably intriguing due to its unique hybrid of historical narrative and biography. Examining this work from the perspective of biographical criticism not only holds scientific significance in elucidating the historical figure of Tang Hsüan-tsang but also sheds light on the activities of Venerable Thich Minh Chau through their notable similarities. This underscores Venerable Thich Minh Chau’s innovative contributions to storytelling and narrative structure, particularly when examined through the framework of biography and culture. By employing biographical criticism and integrating three specialized methods–psychological analysis, socio-cultural context, and interdisciplinary approaches–this paper analyzes the work focusing on biographical elements, travel accounts, and Buddhist studies. The aim is to clarify the depiction of Tang Hsüan-tsang, contributing to the research on Hsuan Tsang, the Pilgrim & Scholar as a resource for Buddhist studies and Vietnamese literature at the university level.